Development of the Pharm‐SAVES educational module for gatekeeper suicide prevention training for community pharmacy staff. - Stover, Amanda N.; Lavigne, Jill E.; Shook, Alexis; MacAllister, Catherine; Cross, Wendi F.; Carpenter, Delesha M. (Health Expectations, 2023)
Introduction: Pharmacists are one of the most accessible health professionals in the United States, who, with training, may serve as gatekeepers who recognize suicide warning signs and refer at‐risk individuals to care. Our objective was to codesign a 30‐min online gatekeeper training module (Pharm‐SAVES) specifically for community pharmacy staff. Methods: Over a period of 8 months, a nine‐member pharmacy staff stakeholder panel and the Finger Lakes (New York) Veterans Research Engagement Review Board each worked with the study team to codesign Pharm‐SAVES. Formative data from previous interviews with community pharmacists were presented to the panels and guided website development. Results: Four key topics were identified for brief skills‐based modules that could be delivered asynchronously online. To help pharmacy staff understand their opportunities as gatekeepers in suicide prevention, statistics and statements from the Joint Commission and pharmacy professional organizations were highlighted in Module 1 ('Why Me?'). Module 2 ('What can I do?') presents the five gatekeeping steps (SAVES): (1) Recognize suicide warning Signs, (2) Ask if someone is considering suicide, (3) Validate feelings, (4) Expedite referral, and (5) Set a reminder to follow‐up. Module 3 ('How does it work?') provides three video scenarios modeling SAVES steps and two interactive video cases for participant practice. Module 3 demonstrates use of the 24/7 National Suicide Prevention Lifeline, including the DOD/VA Crisis Line. Module 4 (Resources) includes links to national resources and a searchable zip code‐based provider directory. Pharm‐SAVES was codesigned with pharmacy and veteran stakeholders to deliver brief, skills‐focused, video‐based interactive training that is feasible to implement in busy community pharmacy settings. Conclusion: Pharm‐SAVES is a brief, online suicide prevention gatekeeper training program codesigned by researchers, community pharmacy and veteran stakeholders. By actively engaging stakeholders at each stage of the design process, we were able to create training content that was not only realistic but more relevant to the needs of pharmacy staff. Currently, Pharm‐SAVES is being evaluated in a pilot randomized controlled trial for changes in pharmacy staff suicide prevention communication behaviors. Patient or Public Contribution: Stakeholder engagement was purposefully structured to engage pharmacy staff and pharmacy consumers, with multiple opportunities for study contribution. Likewise, the involvement of patient/public contribution was paramount in study design and overall development of our study team.